Prevalence Characteristics Risk Factors and Prognosis of Active Epilepsy in Children with Cerebral Palsy. A Prospective Case Control Hospital Based Study - Deeb, Dr Hanan Said; Dr Walid EL (Journal of Medical Biomedical and Applied Sciences, 2014)
Cerebral palsy is a major cause of childhood disability and has been described as one of the three most common life-long developmental disabilities in childhood. It is more prevalent in the more socio-economically deprived populations of the world. Epilepsy is said to occur in 15-90% of children with cerebral palsy and this poses additional economic and psychological stress on affected children and their families. Objectives: To study the prevalence, associated risk factors, and prognosis of seizures in children with cerebral palsy.Methods& Results: A prospective hospital based Case control study done over a period of two years to observe the clinical profile of epilepsy in children with cerebral palsy. Two hundred epileptic children with cerebral palsy were studied and their results were compared with the results of epilepsy in 55 developmentally normal children. Appropriate statistical tests were carried out using the SPSS 12 for windows software to identify significant predictors of epilepsy. Ages of all children studied were between 1-5 years. Majority were below three years of age and male outnumbered female. Spastic Tetraplegia (34.3%) was the commonest type of cerebral palsy. Generalized tonic-clonic seizure (42.8%&45.5%) was the commonest seizure type in both groups respectivey. Second most common type of seizure was partial (21.8%&21.4%) in developmentally normal and cerebral palsy children respectively. Brain atrophy (71.4%) was the commonest computed tomographic findings in cerebral palsy patients. In electro encephalography generalized epileptiform activity was the commonest finding in both groups. Clinical pattern is different in many ways when epilepsy is associated with cerebral palsy.Conclusion: Epilepsy is a frequent problem in children with cerebral palsy. A history of neonatal seizures, occurrence of seizures in the first year of life, presence of spastic tetraplegia and post infectious brain damage all warrant a close evaluation and appropriate follow up for early detection of epilepsy in children with cerebral palsy. Key words: Epilepsy, risk factors, cerebral palsy.